Access-based consumption revisited - Bardhi, Fleura; Eckhardt, Giana; Vignali, Greta (Journal of the Academy of Marketing Science, 2026)
Abstract Access-based consumption, defined as transactions that may be market mediated in which no transfer of ownership takes place, is conceptualized by Bardhi and Eckhardt (2012). While it was introduced to explore consumer engagement in the sharing economy, conceptually it challenges the dominant assumption of ownership in marketing. This paper reflects on the impact of ABC and its boundary conditions. We critically interrogate and expand on five challenges of the original concept: the static dichotomy of access versus ownership; its transactional framing; its lack of identity value; its treatment of ideology; and its reliance on one context. We discuss the implications of ABC for marketing research related to: a prosumer role of the consumer; its ambivalent responsibility and governance; the bundled, or layered notions of access/ownership for digital ownership; as well as its implications for platformized consumption, which reinforces its instrumental sociality, and where value is extracted through data rather than ownership.